Multiple Intelligence-based basketball performance assessment in high school - Huda, Nurul; Sukarmin, Yustinus; Dimyati, Dimyati (Graduate School, Universitas Negeri Yogyakarta in cooperation with Himpunan Evaluasi Pendidikan Indonesia (HEPI) Yogyakarta, 2022)
This study aims to develop performance assessment instruments in the MI (Multiple Intelligences) based basketball game by: (1) proving the validity of the content of the instrument, (2) proving the validity of the instrument construct, (3) conducting a model fit analysis and item fit with IRT (Item Response Theory), and (4) analyzing the effectiveness of the developed instrument product. Methods in developing assessment models using IDDIE (analysis, design, development, implementation, and evaluation). The research subjects used were 1053 students in five schools in five districts in Yogyakarta Province. The development of a scoring model resulted in (1) the validity of the contents of the five raters using the V-Aiken method yielding a value of 0.92; (2) the validity of the performance instrument construct shows 28 aspects of the warning with a loading factor of >0.3; (3) the fit model for this instrument matches the ability of the learner between -4.817 to 2.24; (4) the effectiveness of the product showed a high value, i.e., 38% of users felt